EU merger control database: 1990-2014 - Pauline Affeldt; Tomaso Duso; Florian Szücs (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
[Introduction] Competition policy, i.e. the design and enforcement of competition rules, is a cornerstone of European Union policy designed to enhance European integration and foster growth. Among the different areas of the European Commission's (EC) antitrust enforcement, i.e. collusion, merger, and abuse-of-dominance cases, this dataset focuses on EC merger policy. As common European merger control started in 1990, we can now look back at, and evaluate more than 25 years of EC merger control. We collected data on almost the complete population of the Directorate-General Competition's (DG COMP) merger decisions, both across time and with regard to the scope of the decisions encompassed. We started data collection with the very first year of common European merger control, 1990, and included all years up to 2014. This amounts to 25 years of data on European merger control. With regard to the scope of the decisions, we collected data in all cases where a legal decision document exists. This includes all cases settled in the first phase of an investigation (Art. 6(1)(a), 6(1)(b), 6(1)(c) and 6(2)) and all cases decided in the second phase of an investigation (Art. 8(1), 8(2), and 8(3)). Note that this also includes all cases settled under a `simplified procedure', provided that a legal decision document exists. Furthermore, we also intended to collect data on cases that were either referred back to member states by DG COMP or aborted by the merging parties. While we have collected some data on such cases, data on these cases is not always available. Therefore, we cannot guarantee that the final dataset covers all of these cases. Rather than taking a particular merger case as the level of observation, we decided to collect data at a more fine-grained level, defining an observation as a particular product/geographic market combination concerned by a merger. In total, the final dataset contains 5,196 DG COMP merger decisions, where each decision occupies a number of rows equal to the number of product/geographic markets identified in the specific transaction. Hence, the total dataset contains 31,451 observations. The remainder of the data documentation is structured as follows. In section 2, we provide a short overview of DG COMP's merger review process. In section 3, we describe how we collected and recorded the merger data, in section 4, we describe our data cleaning and quality control procedure. Section 5 contains a description of all the variables included in the final database. Lastly, we explain the data collection procedure with the help of an example case in section 6.
Keywords: 330